More on the spider genus Xeropigo O.P.-Cambridge (Araneae, Corinnidae, Corinninae): seven new species and new records from Brazil - Carvalho, Leonardo S.; Shimano, Yulie; Candiani, David F.; Bonaldo, Alexandre B. (Zootaxa, 2016)
Seven new species of the spider genus Xeropigo O. P.-Cambridge are described from Brazil, increasing the genus member list up to 16 species. X. piripiri n. sp., X. aitatu n. sp., and X. cajuina n. sp. are described from the state of Piauí. X. crispim n. sp. is described from the states of Ceará, Piauí, and Maranhão. X. oxente n. sp. is described from the state of Rio Grande do Norte. X. canga n. sp. is described from the state of Minas Gerais. X. ufo n. sp. is described from the state of Mato Grosso. The geographical distribution of X. tridentiger, X. camilae, X. pachitea, and X. perene is updated. A key to all species of Xeropigo is presented and possible relationships among all species of the genus are discussed.